2013
DOI: 10.1097/ta.0b013e318278918a
|View full text |Cite
|
Sign up to set email alerts
|

A, B, C, D, echo

Abstract: Diagnostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…With the cutoff of 40 %, the IVC collapsibility index that is maximum IVC diameter minus minimum IVC diameter divided by maximum IVC diameter times 100 % would only give a sensitivity of 70 %, specificity of 80 %, positive predictive value of 72 %, and negative predictive value of 83 % [ 30 ]. In trauma patients with hemorrhage, IVC measurement in addition to FAST is also helpful for managing trauma patients with hypovolemia to guide fluid therapy and shorten the time to operation theater [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the cutoff of 40 %, the IVC collapsibility index that is maximum IVC diameter minus minimum IVC diameter divided by maximum IVC diameter times 100 % would only give a sensitivity of 70 %, specificity of 80 %, positive predictive value of 72 %, and negative predictive value of 83 % [ 30 ]. In trauma patients with hemorrhage, IVC measurement in addition to FAST is also helpful for managing trauma patients with hypovolemia to guide fluid therapy and shorten the time to operation theater [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 16 ) Ferrada et al, reported US-based management changes in 96% of cases involving trauma patients aged over 65 years. ( 17 ) Hemodynamic resuscitation can also be easily be performed in all cases under US guidance, as it allows determination of crystalloid or vasoactive drug needs in shock reversion. ( 18 - 20 )…”
Section: Discussionmentioning
confidence: 99%
“…As POCUS is a relatively new diagnostic and procedural modality, previous literature has focused on investigating its emerging indications and clinical utility, and emphasis was more on demonstrating its advantage over physical examination alone [ 1 11 ]. Therefore, less attention was paid to the timing of POCUS and how POCUS is best incorporated in the clinical workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound (POCUS) is a rapidly evolving diagnostic modality that is performed and interpreted by providers at the bedside [ 1 7 ]. An increasing number of reports have shown that POCUS can modify diagnoses, direct further testing, and change medical therapy [ 8 19 ].…”
Section: Introductionmentioning
confidence: 99%